BUMN Sebagai Pemungut Pajak Pertambahan Nilai: Studi Kasus PT. Hutama Karya (PERSERO) - Jeffits Khusnu Alif; Fitrawansah; Evi Harviani; Aam Azatil Isma; Sri Aisyah Yope (Program Studi Akuntansi, Fakultas Ekonomi, Universitas Islam Majapahit, 2023)
Value Added Tax (PPN) is a type of tax that is levied directly by the government through State-Owned Enterprises (BUMN) as an intermediary for state business activities, in accordance with Minister of Finance Regulation No. 37/PMK. 03/2015, PT. Hutama Karya (Persero), which is a state-owned company in the field of construction services, is also a VAT collector for WaPu as well as a VAT taxpayer. This study uses an interpretive qualitative approach with a case study method, because it aims to find out the problems contained in the collection of VAT in SOEs in the field of construction services, especially PT. Hutama Karya (Persero). There are three problems in the Indonesian tax system, namely; The first is that there is no clarity on the rights or incentives obtained by SOEs, the second problem is, the process of restitution or refund of VAT overpayments which takes a long time, and the third problem is the tax fines that arise when SOEs are late in depositing VAT to the state.